AN ANALYSIS OF THE STUDENTS’ GRAMMAR DIFFICULTIES IN USING NOUN CLAUSE AT SECOND YEAR STUDENTS’ OF AKADEMI PARIWISATA JAKARTA - Edri Edri (Dharmas Education Journal (DE_Journal), 2021)
Noun clauses are a component that needs to be learned in English. According to the 2004 curriculum or the Competency Based Curriculum (KBK) in English subjects, noun clauses are taught to University students in Semester IV, so this research was conducted to look at the difficulties of students in Semester IV using noun clause in reading and combining two sentences into one sentence. The form of this research is a study that describes a phenomenon that actually occurred in the field with a population of 60 students in Akademi Pariwisata Jakarta. So population taking, the authors use cluster random sampling to get valid and reliable tests, the authors carry out try out in classy classes. To try out the writer took data in Semester IV. The form of this research instrument is a written test. The test is in the form of multiple choice (multiple choice) consisting of 40 questions. These questions have been tested before, and then the questions were made into test questions for data collection after collecting data and deceiving data, the writer gets a percentage of students' ability scores in using Noun Clause 57.5% while students have difficulty using noun clause 42%, then students have difficulty using Noun Clause in learning English. Each category where the use of noun clauses. Which students get 41.48 who 42.14, whom 32.22, that 45.24, where 63.33 what 40.00 when 38.89 whose 41.67. Then the percentage of each category is generally greater than 40%, so the conclusion is that the Students of semester IV of Akademi Pariwisata Jakarta find the difficulty to use noun clauses caused by lack of facilities, vocabularies and motivation in studying English.